(untitled) (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Kaewgrajang T, Yamato M, Polamart T, Sangwanit U. 2023. A comparison between the ectomycorrhizal fungal communities associated with the natural and plantation populations of Dipterocarpus alatus. Biodiversitas 24: 2088-2098. Dipterocarpus alatus Roxb. is a native tree species of Southeast Asian countries and one of the most economically important dipterocarp species. We investigated the ectomycorrhizal (ECM) fungi associated with D. alatus using molecular identifications on putative fruiting bodies and ECM roots collected from three natural forests and 10 D. alatus plantations. In this investigation, we aimed to report the ECM fungal communities of D. alatus in natural forests and plantations. Combining the results of fruiting bodies and ECM roots, 82 taxa belonging to 12 families were identified as ECM fungi. The ECM fungal community comprised many rare species and a few frequently found species. The Sebacina genus was found the most frequently in natural forests and plantations. The ECM fungal diversity was higher in plantations compared to natural forests. However, the frequently occurring ECM fungal taxa were not different between the natural forests and plantations. The result suggests that ECM fungal communities could be maintained in D. alatus plantations even if a reduction occurs in the natural population of dipterocarp forest.